INSONIYATGA QARSHI JINOYATLAR - ALLABERGANOVA BARNO UMID QIZI (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article shows that the rights of young people and morals in the family, that is, human rights, are first of all enshrined in the Constitution of the Republic of Uzbekistan, that the main direction of our Constitution is to glorify man and his life, man and his life, freedom, honor, dignity is dedicated to clarifying that the value and other inviolable rights are considered to be of the highest value.